Blood Supply Classification and Varied Clinical Manifestations of Skeletal Muscle Infarction. (May 2015) - Lai, Ya-Wei; Lee, Su-Shin; Chang, Kao-Ping; Huang, Shu-Hung; Lin, Yu-Nan; Lin, Sin-Daw; Lai, Chung-Sheng
Abstract : Background: Muscle infarction is a rare complication of spontaneous ischemic necrosis occurring in skeletal muscle. It is particularly common in patients with diabetes who have impaired sugar regulation. However, muscle infarction is frequently misdiagnosed due to varied clinical manifestations. Methods: We presented 3 cases of muscle infarction reported during April 2009 to April 2014. After a comprehensive literature review, we selected 147 muscle infarction cases from the literature, first investigating the relationships between type of muscle blood supply and infarcted muscle. Results: The result indicated that muscle infarction 25.85 % belonged to type I vascular supply and 61.21% belonged to type II vascular supply, according to the definition by Mathes and Nahai. Conclusions: Poor glucose regulation, intense exercise without adequate hydration, vascular disease, and type I and II muscular blood supply were critical predisposing factors. For preventing muscle infarction, we recommend strict glucose regulation and a gradual increase in exercise with adequate hydration.